Transition Models in a Non-Stationary Environment - Imbens, G. W. (The Review of Economics and Statistics, 1994)
An alternative form of the proportional hazard model is proposed. It allows one to introduce correlation between exit rates at the same (calendar) time for different individuals. One can, in the context of this model, still allow for, and estimate, duration effects. These should be parametrized. These modifications to the original Cox model are possible by reversing the roles of duration and calendar time. It is argued that flexibility with respect to the effects of these macro processes is of particular relevance in economic models. An example using Dutch data on labor market transitions illustrates the idea that to ignore calendar time effects may have severe consequences for the estimation of duration dependence. Copyright 1994 by MIT Press.